Memories of the school in the Quilombo Negros do Riacho, located in Currais Novos, Rio Grande do Norte, Brazil (Research, Society and Development, 2019)
The present article responds to the proposal of work of research of the memories of the school in Quilombo Negros do Riacho-RN. The essay presents in its first part a motivation to talk about the memory of the Quilombo Negros do Riacho school, from thinkers such as Asunción (2009), Le Goff (1992), Halbawachs (1990) and Pierre Nora (1984). As results, a brief report is presented on the formation of the Quilombo Negros do Riacho, the Memory and History of the Negros do Riacho Community School process, where the school's operating locations and its evolution are presented. It is proposed to present some transformations that happened in the school over time and that in the present collaborate to the understanding of the Memory and History of the School in the community. In the considerations are looked for to trace ways for the development and improvement of the community and the preservation of the memory. The methodology was made through qualitative research using reports from teachers, former school students belonging to the quilombola community in open interviews and theoretical reference that justifies the construction of a memory and history.